The guardstone spiders of the genus Phonotimpus Gertsch & Davis (Araneae: Phrurolithidae) from northeastern Mexico - Platnick, Norman I.; Chamé-Vázquez, David; Ibarra-Núñez, Guillermo (Zootaxa, 2022)
The American genus Phonotimpus Gertsch & Davis, 1940 (Araneae, Phrurolithidae) was described on the basis of two species from northern Mexico. Recently, four species were described from Central and South Mexico and one species was transferred to this genus. Here we describe the males of Phonotimpus separatus Gertsch & Davis (the type species) and P. eutypus Gertsch & Davis, both previously known only from female specimens. Moreover, we describe 25 new species from Northeast Mexico (Nuevo León, Tamaulipas, and San Luis Potosí): P. ahuacatlan sp. nov., P. arcitos sp. nov., P. boneti sp. nov., P. calenturas sp. nov., P. chipinque sp. nov., P. cielo sp. nov., P. cima sp. nov., P. cuauhtemoc sp. nov., P. cumbres sp. nov., P. elviejo sp. nov., P. escondida sp. nov., P. farias sp. nov., P. frio sp. nov., P. gertschi sp. nov., P. llera sp. nov., P. perra sp. nov., P. pozas sp. nov., P. puente sp. nov., P. revilla sp. nov., P. sanpedro sp. nov., P. vacas sp. nov., P. valles sp. nov., P. taman sp. nov., P. tetrico sp. nov. and P. xilitla sp. nov. Furthermore, we propose five species groups that include almost all of the new species and all the species described to date.